Transcriptomic and physiological analysis reveals the possible mechanism of ultrasound inhibiting strawberry (Fragaria × ananassa Duch.) postharvest softening - Zhang, Junyi; Jiang, Hui; Li, Yutong; Wang, Shaojia; Wang, Bei; Xiao, Junsong; Cao, Yanping (Frontiers in Nutrition, 2022)
Ultrasound effectively inhibited strawberry softening but the mechanism was not clear. In this study, physical data including firmness, soluble pectin (SP) contents, pectin esterase (PE), polygalacturonase (PG) activity and transcriptome sequencing data were analyzed to explore the mechanism of strawberry response to ultrasonic treatment. After 24 days storage, the firmness reduction rate and soluble contents (SP) increased rate of the strawberry treated with ultrasound (25 kHz, 0.15 W/cm2) for 3 min decreased 41.70% and 63.12% compared with the control, respectively. While the PG and PE enzyme activities of ultrasound-treated strawberries were significantly lower than control after storage for 18 days. A total of 1905 diferentially expressed genes (DEGs) were identified between ultrasound-treated and control, with 714 genes upregulated and 1254 genes downregulated, including 56 genes in reactive oxygen species (ROS), auxin (AUX), ethylene (ETH) and jasmonic acid (JA) signaling pathways. At 0h, 15 genes including LOX, JMT, ARP, SKP, SAUR, IAA, ARF and LAX were significantly upregulated compared with the control group, which means reactive oxygen specie, auxin, ethylene and jasmonic acid-mediated signaling pathway respond to ultrasound immediately. ERF109, ERF110 and ACS1_2_6 downregulated before 2 days storage indicated ethylene signaling pathway was inhibited, while after 2 days, 9 genes including ERF027, ERF109 and ERF110 were significantly upregulated indicating that the response of the ethylene signaling pathway was lagging. Therefore, in strawberry ultrasound enhanced ROS scavenging and activated JA biosynthesis, which acts as a signal for delaying the activation of ET signaling pathway, thus suppressing the activity of pectin-degrading enzymes PE and PG, and ultimately inhibiting postharvest softening.